The Unsolvability of Multiplicative Inverse Eigenvalue Problems Almost Everywhere (Journal of Computational Mathematics, 2018)
The idea and technique used in [7] are applied to the multiplicative inverse eigenvalue problems as well. Some sufficient and necessary conditions that the multiplicative inverse eigenvalue problems be unsolvable almost everywhere are given. The results are similar to those of [7], but the proofs are more complicated.